Analisis Kemampuan Koneksi Matematis Peserta Ddidik Kelas I pada Pembelajaran Bangun Datar di Sekolah Dasar - Muhammad Farhan; Chandra Chandra; Salmaini Safitri Syam (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
Mathematical connection ability is a crucial competence that should be developed from the elementary level, as it helps students understand the interrelationships between mathematical concepts and their applications in daily life. This study aims to analyze the mathematical connection abilities of first-grade elementary school students in learning flat shapes. The research employed a descriptive quantitative method using cognitive and psychomotor assessment instruments. The cognitive test consisted of multiple-choice and essay questions measuring students' ability to recognize, understand, classify, and apply flat shapes. The psychomotor test involved tasks such as assembling flat shapes into meaningful objects and classifying shapes by type. The results showed that students were fairly capable of identifying and grouping flat shapes, but had difficulty explaining classification reasons or relating shapes to real-life objects. The psychomotor results also indicated that fine motor skills and the ability to make real-world connections need improvement. These findings highlight the importance of contextual learning approaches and the use of concrete media to strengthen students’ mathematical connections from an early age.